Encapsulation of bacillus salmalaya 139si using biopolymer to improve growth of Zea mays / Pravin Vejan - Pravin , Vejan (2019)
Sustainable crop production for rapidly growing human population is one of the challenges faced globally by agricultural sector nowadays. Therefore, mass production and utilization of chemical based fertilizers became rampant due to its role as an essential plant growth agents to maximize agricultural productivity. However, most of the fertilizers can be hazardous to humans, deterioration of soil fertility and eutrophication. As an alternative, the use of plant growth promoter based bacteria plays a role in supporting the plant growth under various stress condition. Unfortunately, bacteria activities decrease due to temperature and environmental factors. Therefore, this study was carried out to develop the encapsulation of Bacillus salmalaya 139SI using simple double coating bio-polymer technique which consists of brown-rice protein/alginate capsules coated with 0.5% low molecular weight chitosan. The influence of bio-polymer to bacteria mass ratio, concentration of cross-linker and pH of chitosan on the encapsulation process, physico-chemical, morphology and bioactivity properties of encapsulated Bacillus salmalaya 139S1 have been studied systematically. The optimized encapsulated bacteria were applied on maize plantation to investigate the growth performance, soil fertility and nutrient uptake in glasshouse condition. The treatments were arranged in randomized complete block design (RCBD) with 11 treatments and 4 replications consists of control, NPK fertilizer only, bio-fertilizers containing beneficial microorganisms (Bacillus salmalaya), encapsulated Bacillus salmalaya in slurry (wet) form and in powder (dry) form. Application of bio-fertilizer, encapsulated Bacillus salmalaya in slurry (wet) form and in powder (dry) form were applied with 3 different percentage which is 100%, 70% bio-fertilizer: 30% NPK, and 50% bio-fertilizer: 50% NPK, respectively. Bacillus salmalaya have been successfully encapsulated and it is identified that biopolymers formulation of 2% of sodium alginate with 1% of brown rice protein isolates cross-linked by 0.15M calcium chloride and finally double coated with 0.5% chitosan of pH 6 is the best optimized formulation out of 8 formulations. The slurry (wet) form of capsules yielded 7.48 log cfu/ml with encapsulation yield of 99.7% and the same freeze-dried slurry formulation yielded 6.8 log cfu/ml with encapsulation yield of 89.3%. This is further morphologically confirmed by the presence of bacteria rod-like structures on the crushed layer of capsules under magnification. In glasshouse study, the maize plants treated with encapsulated Bacillus salmalaya in slurry form showed a significantly increased (p<0.05) in term of growth performance parameter, diameter of stem (12.63cm) and dry weight (15.72g), root length density (9.02cm) followed by encapsulated Bacillus salmalaya in powder (dry) form, only Bacillus salmalaya, NPK fertilizer and lastly control. Correlation showed there are relationships between soil properties and plant biomass. Furthermore, a correlation showed nutrient uptake by maize is positive correlated with dry weight of maize. It was observed that the usage of the combination of NPK fertilizer together with the encapsulated slurry Bacillus salmalaya in slurry (wet) form in ratio 50% encapsulated bio-fertilizer: 50% NPK indicated as the best treatment in promoting plant growth, nutrient uptake and enrich the soil. Encapsulation of bacteria into core-shell biopolymer is a promising technique to overcome the problem.